2012
DOI: 10.1097/fjc.0b013e31824485dd
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Integration of In Vivo Cardiovascular Models During Lead Optimization

Abstract: The strategic integration of in vivo cardiovascular models is important during lead optimization to enable a wide therapeutic index for cardiovascular safety. However, under what conditions (eg, species, route of administration, anesthesia) studies should be performed to drive go/no-go is open to interpretation. Two compounds, torcetrapib and a novel steroid hormone mimetic (SHM-1121X), both with off-target cardiovascular liabilities, were profiled in 4 in vivo cardiovascular models. Overlapping plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Hemodynamics, including blood pressure and heart rate, represent important safety pharmacology endpoints with well-established correlation to clinical observations in man (Authier et al, 2015 ). This has been demonstrated in multiple studies across therapeutic classes and drug mechanisms, and perhaps is most referenced in regard to the off-target effects of the CETP blocker, torcetrapib (Polakowski et al, 2009 ; Fryer et al, 2012a ; Al-Saffar et al, 2015 ), a molecule that was terminated during late-stage clinical development after demonstration of higher cardiovascular events and mortality in patents and that was associated with small magnitude changes in systolic pressure (4 mmHg) both clinically and pre-clinically (as reviewed in Authier et al, 2015 ). Cardiovascular safety pharmacology testing can be performed under acute or chronic dosing conditions to probe underlying risk for effects of differential underlying etiology (e.g., acute modulation of blood pressure provoked by changes in vascular tone vs. chronic modulation of blood pressure due to alterations in Na + balance) (Fryer et al, 2012c ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hemodynamics, including blood pressure and heart rate, represent important safety pharmacology endpoints with well-established correlation to clinical observations in man (Authier et al, 2015 ). This has been demonstrated in multiple studies across therapeutic classes and drug mechanisms, and perhaps is most referenced in regard to the off-target effects of the CETP blocker, torcetrapib (Polakowski et al, 2009 ; Fryer et al, 2012a ; Al-Saffar et al, 2015 ), a molecule that was terminated during late-stage clinical development after demonstration of higher cardiovascular events and mortality in patents and that was associated with small magnitude changes in systolic pressure (4 mmHg) both clinically and pre-clinically (as reviewed in Authier et al, 2015 ). Cardiovascular safety pharmacology testing can be performed under acute or chronic dosing conditions to probe underlying risk for effects of differential underlying etiology (e.g., acute modulation of blood pressure provoked by changes in vascular tone vs. chronic modulation of blood pressure due to alterations in Na + balance) (Fryer et al, 2012c ).…”
Section: Resultsmentioning
confidence: 97%
“…Male Wistar Han rats ( n = 8/dose) were instrumented with telemetry transmitters (DSI, St. Paul, MN) as previously described (Fryer et al, 2012a ) to continuously record hemodynamic parameters while conscious and freely moving after oral administration. Group size was based on prior experience with the model and as previously described (Fryer et al, 2012b ).…”
Section: Methodsmentioning
confidence: 99%
“…Acute administration two differentially selective S1P agonists, FTY720 and BAF312 (more selective S1P1,5 agonist) to Sprague Dawley rats resulted in S1P1-mediated bradycardia. However, administration of FTY720, but not BAF312, resulted in caused dose-dependent hypertension mediated by S1PR3 (46). In addition, oral administration of FTY720 in SHR rats, but not in Wistar Kyoto rats, increased the mean arterial pressure and induced large contractions in isolated carotid arteries, most probably due to the inhibition of sphingosine kinase (47).…”
Section: Sphingolipids In Cardiovascular Diseases Hypertensionmentioning
confidence: 89%
“…Recently, an analysis of the Cardiovascular Health Study population without a history of atrial fibrillation revealed that plasma ceramides and sphingomyelins with very long chain saturated fatty acids were associated with a reduced risk of incident atrial fibrillation, whereas ceramides and sphingomyelins with palmitic acid were associated with an increased atrial fibrillation risk (180). Moreover, in clinical settings, treatment with S1P receptor modulators was associated with side effects, such as bradycardia, atrioventricular blocks, and also probably ventricular tachycardia, which were suggested to be mainly S1PR1/S1PR3-dependent (46,(181)(182)(183)(184). In addition, patients with atrial fibrillation had significantly lower plasma concentration of S1P in comparison with the controls with sinus rhythm, however, the exact role of S1P in atrial fibrillation needs to be further investigated (185).…”
Section: Arrhythmias and Conduction Disordersmentioning
confidence: 99%